Molecules containing lewis acidic phosphorus - sites - Ilic, Gordana (2018)
Carbones (CL2) are a group of ligands with a divalent carbon(0) center. Due to the two available electron-pairs, carbones are considered to be substantially basic, which allowed them to serve as stabilizing ligands for a variety of the highly labile species. In this work, we report the synthesis of [(Ph3P)2CPNiPr2]2+, its two additional analogues [((RPh2P)2C)P(NR′2)]2+ (R = Ph, R′ = Cy; R = 1/2 (CH2)3, R′ = iPr;), and we explore its viability in the presence of various counterions. In addition, the oxophilic nature of [(Ph3P)2CPNiPr2]2+ is further studied in reactions with pyridine N-oxide (PyO). Surprisingly the resulting oxophosphonium dication proved to be an intermediate for the subsequent Baeyer-Villiger (BV)-resembling oxidation reaction, which proceeds through a Criegee intermediate to finally yield a rare P-C bond activation under mild conditions. Apart from being the first example of a PyO-driven BV oxidation, it is a safer alternative to the formerly used highly reactive mchlorobenzoic acid and hydrogen-peroxide. These results inspired us to also develop a route to the elusive parent-metaphosphonate species. This thesis also covers the synthetic pathway and the reactivity of the first carbone-stabilized parentmetaphosphonate [(Ph3P)2CP(O)2H].